2009
DOI: 10.1016/j.jpsychires.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of neurosteroids in obsessive compulsive disorder

Abstract: Alterations in hormone concentrations, including adrenocorticotropin, corticotropin releasing hormone, and cortisol have been reported in patients with obsessive compulsive disorder (OCD). Dehydroepiandrosterone (DHEA) and its sulfated metabolite, DHEA-S, have not been assessed in patients with OCD. We report 24-hour serum DHEA, DHEA-S, and cortisol concentrations in a young man with OCD and 15 healthy young men. Circadian patterns of DHEA and cortisol were markedly different in the subject with OCD than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…This finding appears to be compatible with central neurotransmitter alterations assumed in OCD, indicating an influence at hypothalamic or higher levels. In a single individual with OCD, the circadian patterns of DHEA and cortisol have been reported to be markedly different from control subjects, with DHEA and DHEA-S levels being substantially higher in the OCD subject (Bigos et al 2009). This preliminary finding requires the assessment of larger patient samples.…”
Section: Hormonal Abnormalities In Ocdmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding appears to be compatible with central neurotransmitter alterations assumed in OCD, indicating an influence at hypothalamic or higher levels. In a single individual with OCD, the circadian patterns of DHEA and cortisol have been reported to be markedly different from control subjects, with DHEA and DHEA-S levels being substantially higher in the OCD subject (Bigos et al 2009). This preliminary finding requires the assessment of larger patient samples.…”
Section: Hormonal Abnormalities In Ocdmentioning
confidence: 99%
“…In a recent review, Kalsbeek et al (2012) have described the current view on the control by the suprachiasmatic nucleus of the daily rhythm in the activity of the hypothalamic-pituitaryadrenal (HPA) axis. Individuals with OCD have been reported to show alterations in hormone levels, including the concentrations of cortisol (Catapano et al 1992;Monteleone et al 1994), corticotrophin releasing hormone (CRH) (Altemus et al 1992), dehydroepiandrosterone (DHEA) and its sulfated metabolite DHEA-S (Bigos et al 2009), adrenocorticotrophic hormone (ACTH) (Bailly et al 1994), growth hormone (Kluge et al 2007a, b), vasopressin (Altemus et al 1992), oxytocin (Leckman et al 1994) and melatonin (Catapano et al 1992;Monteleone et al 1994).…”
Section: Hormonal Abnormalities In Ocdmentioning
confidence: 99%
“…The androgen DHEA is particularly interesting because of its anti-glucocorticoid actions in the brain (Kimonides et al 1998, Cardounel et al 1999, Kimonides et al 1999, Kurata et al 2004, and because adrenal secretion has been shown to be altered in several disease states and psychopathologies (Goodyer et al 2001). For example, decreased plasma DHEA and/or its sulfated derivative DHEAS occurs in patients with rheumatoid arthritis, coronary artery disease, anorexia nervosa, anxiety, depression, and obsessive compulsive disorder (Barrett-Connor et al 1986, Wilder 1996, Goodyer et al 1998, Gordon et al 1999, Wolkowitz & Reus 2000, Harris et al 2001, van Niekerk et al 2001, Bigos et al 2009). HPA axis dysregulation has been described for psychosis in general, and for schizophrenia in particular (Cotter & Pariante 2002), and includes increased basal cortisol secretion (Ryan et al 2004), increased adrenocorticotropic hormone (ACTH)/cortisol responsiveness to the dexamethasone (DEX)/corticotrophic-releasing hormone challenge test (Lammers et al 1995), and increased plasma DHEA concentrations in severely psychotic male subjects and medicated patients with chronic schizophrenia (Oades & Schepker 1994, di Michele et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that monoamines and hormone concentrations could be altered in patients with different psychopathologies, such as generalized anxiety disorder [49,50] and OCD [51][52][53]. Thus, in the present study we also evaluated if grooming expression in the EPM could be correlated with one of these parameters.…”
Section: Discussionmentioning
confidence: 92%